Low-protein diets for chronic kidney disease patients: the Italian experience. Issue 1 (December 2016) - Bellizzi, Vincenzo; Cupisti, Adamasco; Locatelli, Francesco; Bolasco, Piergiorgio; Brunori, Giuliano; Cancarini, Giovanni; Caria, Stefania; De Nicola, Luca; Di Iorio, Biagio; Di Micco, Lucia; Fiaccadori, Enrico; Garibotto, Giacomo; et al.
Abstract Background Nutritional treatment has always represented a major feature of CKD management. Over the decades, the use of nutritional treatment in CKD patients has been marked by several goals. The first of these include the attainment of metabolic and fluid control together with the prevention and correction of signs, symptoms and complications of advanced CKD. The aim of this first stage is the prevention of malnutrition and a delay in the commencement of dialysis. Subsequently, nutritional manipulations have also been applied in association with other therapeutic interventions in an attempt to control several cardiovascular risk factors associated with CKD and to improve the patient's overall outcome. Over time and in reference to multiple aims, the modalities of nutritional treatment have been focused not only on protein intake but also on other nutrients. Discussion This paper describes the pathophysiological basis and rationale of nutritional treatment in CKD and also provides a report on extensive experience in the field of renal diets in Italy, with special attention given to approaches in clinical practice and management. Summary Italian nephrologists have a longstanding tradition in implementing low protein diets in the treatment of CKD patients, with the principle objective of alleviating uremic symptoms, improving nutritional status and also a possibility of slowing down the progression of CKD or delaying the start of dialysis. A renewed interest in this field is based on the aim of implementing a wider nutritional therapy other than only reducing the protein intake, paying careful attention to factors such as energy intake, the quality of proteins and phosphate and sodium intakes, making today's low-protein diet program much more ambitious than previous. The motivation was the reduction in progression of renal insufficiency through reduction of proteinuria, a better control of blood pressure values and also through correction of metabolic acidosis. One major goal of the flexible and innovative Italian approach to the low-protein diet in CKD patients is the improvement of patient adherence, a crucial factor in the successful implementation of a low-protein diet program.